Geometric Properties of Generalized Von Neumann Constant - ZHAO Liang; ZHAO Pingan (Journal of Harbin University of Science and Technology, 2023)
Spatial geometric constant is a quantization of the properties of spatial geometry. In order to further apply the geometric constant to study the geometry of the Banach space, a new generalized von Neumann constant is introduced. We give the continuity, symmetry, boundedness and the equivalent form of the generalized von Neumann constant, and judge the consistent non-square of the Banach space, and give the calculation formula or valuation of several special Banach space with two examples.